2020
DOI: 10.1111/cns.13296
|View full text |Cite
|
Sign up to set email alerts
|

P2Y6 receptor inhibition aggravates ischemic brain injury by reducing microglial phagocytosis

Abstract: Introduction Clearance of damaged cells and debris is beneficial for the functional recovery after ischemic brain injury. However, the specific phagocytic receptor that mediates microglial phagocytosis after ischemic stroke is unknown. Aim To investigate whether P2Y6 receptor‐mediated microglial phagocytosis is beneficial for the debris clearance and functional recovery after ischemic stroke. Results The expression of the P2Y6 receptor in microglia increased within 3 days after transient middle cerebral artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…9 Ischemic stroke perturbs endogenous inhibitory signaling and triggers microglial activation 10 that either aggravates ischemic injury or induces repair and regeneration, depending on the different signals received by microglial receptors. 10,11 TREM2 abundance on the microglia cell surface is 300 times higher than on astrocytes. 12 TREM2, coupled with the transmembrane signaling adaptor DAP12, is involved in physiological processes, including proinflammatory responses and phagocytosis of cell debris from damaged neurons and Aβ protein.…”
Section: Introductionmentioning
confidence: 97%
“…9 Ischemic stroke perturbs endogenous inhibitory signaling and triggers microglial activation 10 that either aggravates ischemic injury or induces repair and regeneration, depending on the different signals received by microglial receptors. 10,11 TREM2 abundance on the microglia cell surface is 300 times higher than on astrocytes. 12 TREM2, coupled with the transmembrane signaling adaptor DAP12, is involved in physiological processes, including proinflammatory responses and phagocytosis of cell debris from damaged neurons and Aβ protein.…”
Section: Introductionmentioning
confidence: 97%
“…On the contrary, Wen and colleagues observed that inflammatory cytokine mRNA expression of IL-1α, IL-1β, IL-6, IL-10, TNF-α and transforming growth factor-beta (TGF-β), both in the in vivo model of stroke and in vitro, did not change with MRS2578, which is a selective P2Y6R antagonist [ 47 ]. This indicates that P2Y6R inhibition only decreased the phagocytic function of microglia, without affecting the inflammatory response [ 47 ].…”
Section: Pathophysiology and Therapeutic Potential Of P2y6rmentioning
confidence: 99%
“…P2Y6R-mediated microglial phagocytosis has been reported to be beneficial for debris clearance and functional recovery after an ischemic stroke [ 47 ]. Briefly, the P2Y6R levels increased significantly in ischemic mice after transient middle cerebral artery occlusion (tMCAO), and the P2Y6R seems to be expressed exclusively in microglia [ 47 ]. Moreover, inhibition of P2Y6R activity exacerbated neurological function deficit and brain injury after tMCAO.…”
Section: P2y6r As a Potential Target In Neurological Diseasesmentioning
confidence: 99%
See 2 more Smart Citations